Prospek Pengembangan Sorgum di Jawa Barat Mendukung Diversifikasi Pangan - Bambang Irawan; Nana Sutrisna (Forum penelitian Agro Ekonomi, 2011)
EnglishOne of issues in Indonesia related with food security is reliance on imported foods, especially wheat and rice. To cope with this issue, development of local food crops substitute to both foods is essential particularly those adapted to dry land characterized by barrenness, high erosion risk, and limited water supply. Sorghum is one of local food crops to these drought characteristics. Use of sorghum as flour for producing processed foods (noodles, breads, cakes, etc.) can substitute up to 15 to 50 percent of wheat flour. Other industrial products, as well as bio-ethanol, can also be produced using sorghum. Sorghum crop waste is contains high nutrients appropriate for animal feed. To encourage sorghum cultivation in the dry land it is necessary to apply an integrated agribusiness, namely sorghum plant, flour processing, bio ethanol processing, and cattle farming, conducted in a large scale. Development of sorghum processing industries is essential in expanding sorghum market as well as its economic value. In the same time cattle farming is essential to maintain dry land fertility. As an initial stage, this integrated business should be conducted by BUMN (government own companies) facilitated by subsidized investment credit. IndonesianSalah satu masalah yang dihadapi Indonesia berkaitan dengan ketahanan pangan adalah ketergantungan terhadap bahan pangan impor terutama beras dan gandum. Untuk mengatasi masalah tersebut maka perlu dikembangkan bahan pangan lokal lain yang dapat mensubstitusi kedua bahan pangan tersebut dan dapat dikembangkan pada lahan kering yang umumnya memiliki kesuburan rendah, peka terhadap erosi dan ketersediaan air terbatas. Sorgum merupakan tanaman pangan lokal yang dapat dikembangkan pada lahan kering dan penggunaan tepung sorgum untuk pembuatan berbagai produk makanan olahan (mie, roti, kue, dst) dapat mensubstitusi 15%-50 persen tepung gandum. Berbagai produk industri lainnya dan bioetanol juga dapat dibuat dari sorgum sementara limbah tanaman sorgum  bernilai gizi tinggi untuk bahan pakan ternak. Untuk mendorong pengembangan tanaman sorgum di lahan kering perlu diterapkan sistem usaha yang terintegrasi : tanaman sorgum - pengolahan tepung sorgum – pengolahan bioetanol - ternak sapi dalam skala luas. Pengembangan industri pengolahan sorgum diperlukan untuk meningkatkan nilai ekonomi dan memperluas pasar sorgum sedangkan pengembangan ternak sapi diperlukan untuk mempertahankan kesuburan lahan kering. Sebagai inisiasi, pengembangan usaha yang terintegrasi tersebut perlu dilaksanakan oleh BUMN yang difasilitasi dengan subsidi kredit investasi.